2007
DOI: 10.1177/0020764006075022
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Of Depression And Correlates Of Depressive Symptoms For Residents In The Urban Part Of Jeju Island, Korea

Abstract: The prevalence of depression and depressive symptoms in urban Jeju Island is similar to that in a nation-wide sample. By providing intensive mental health services to those who have high stress levels, problem drinking, and poor health behavior, early detection of depressive symptoms in the community will be important for improving general health status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…The prevalence of being in a category at risk for clinical depression (a CES-D score of ≥ 16) was approximately 41.1%. In comparison with other studies, two other cut-off points were also used: scores over 21 (for an elevated level of depressive symptoms) and over 25 (for a level of depressive symptoms comparable with major depressive disorder) [16,17]. Accordingly, approximately one fourth (25.9%) of the students were classified as having an elevated level of depressive symptoms, while 18.7% demonstrated a level of depressive symptoms consistent with major depressive disorder.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of being in a category at risk for clinical depression (a CES-D score of ≥ 16) was approximately 41.1%. In comparison with other studies, two other cut-off points were also used: scores over 21 (for an elevated level of depressive symptoms) and over 25 (for a level of depressive symptoms comparable with major depressive disorder) [16,17]. Accordingly, approximately one fourth (25.9%) of the students were classified as having an elevated level of depressive symptoms, while 18.7% demonstrated a level of depressive symptoms consistent with major depressive disorder.…”
Section: Resultsmentioning
confidence: 99%
“…The standard cut-off score of 16 was used to detect possible cases of depression [15]. For comparison with other studies, two other cut-off points were also used: scores over 21 (for depressive symptoms) and over 25 (for depression) [16,17]. …”
Section: Methodsmentioning
confidence: 99%
“…Depression is a disorder that can be reliably diagnosed and treated in primary care: as outlined in the World Health Organization (WHO) mhGAP Intervention Guide (12), preferable treatment options consist of basic psychosocial support combined with antidepressant medication or psychotherapy, such as cognitive behavior therapy, interpersonal psychotherapy or problem-solving treatment. Looking at gender, depression also strikes more women than men: its prevalence is one to five times greater in females (13)(14)(15)(16)(17)(18)(19). This gender gap can be explained by genetic, neurohormonal, psychobiological (20) and social factors (21), the latter far more predictive of gender gaps in depression than genetic or hormonal factors.…”
Section: Introductionmentioning
confidence: 99%
“…Other socio-economic variables that might be considered as determinants of depression are likely to be endogenous. High frequencies of mental disorders are connected with low education (44,45), family income, as it has been already stressed (18,46) and participation in the workforce (47), especially for women. To account for labor market status, a dummy variable assuming a value of 1 if the respondent was an employed woman and 0 otherwise was included as a regressor.…”
Section: Introductionmentioning
confidence: 99%
“…This finding indicated that the prevalence of depression among Korean women doubled since the previous study [7], which reported that 33.1% of Korean middle-aged women suffered from moderate to severe depression. Other studies also reported a higher prevalence of depression among Korean women than among Korean men: 12.1% vs. 8.1 % [8], 11.4%, and 9.5% [9], respectively. Studies of depressed Korean women in relation to age reported that de-pressive symptoms were highly present, especially among Korean women whose ages ranged from 40 to 60 years [10] and who were 60 and older [11,12].…”
Section: Introductionmentioning
confidence: 81%